Pengaruh Kualitas Audit, Kondisi Keuangan, dan Ukuran Perusahaan Terhadap Opini Audit Going Concern Pada Perusahaan Manufaktur di Sektor Industri Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia - Wilda Kamilia Fitri; Kurnia Indah Sumunar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Business growth in Indonesia provides many innovations to increase the pace of the economy. In this case, not only to generate profits, but also to maintain the company's going concern. This study examines manufacturing companies in the food and beverage industry sector, which aims to determine the effect of audit quality, financial condition, and company size on going concern audit opinion. This research uses a quantitative approach with secondary data taken from the company's 2019–2022 financial statements. A total of 60 data samples were taken and processed using SPSS version 25. The data analysis technique used was descriptive statistical analysis and hypothesis testing through logistic regression analysis. The results of this study indicate that: (a) audit quality influences going-concern audit opinion. Meanwhile (b) financial condition and (c) company size have no effect on going concern audit opinion.